Growth of Nile Tilapia (Oreochromis niloticus) and Giant Freshwater Prawn (Macrobrachium rosenbergii) under Different Legowo Planting Systems in Integrated Rice-Fish Culture - Raihan Ramadhan HSB; Yusran Ibrahim; Mahendra Mahendra (Universitas Teuku Umar, 2026)
Minapadi is an integrated fish farming system carried out in rice fields concurrently with rice cultivation. The purpose of this study was to enhance farmers' income, boost rice productivity, and support the cultivation of endemic fish species. The research employed an experimental approach using a Completely Randomized Design (CRD), consisting of four treatments and three replications. The treatments included: A1B1 (giant prawns with a legowo 2:1 planting system), A1B2 (tilapia with a legowo 2:1 system), A2B1 (giant prawns with a legowo 4:1 system), and A2B2 (tilapia with a legowo 4:1 system). This study was conducted over a period of 90 days (3 months) in rice fields located in Lango Village, Pante Ceureumen District, West Aceh Regency. Three key parameters were observed: rice yield, fish survival rate, and fish growth. The results showed an average rice yield of 5 kg per plot. The best growth performance for prawns was observed in treatment A2B1, with an average weight of 3.62 grams. Meanwhile, the highest growth for tilapia was recorded in treatment A1B2, averaging 19.56 grams. Overall, the findings indicate that applying the Minapadi system with giant prawns and tilapia has a significant positive impact on the observed variables (P<0.05) and holds potential to improve farmers' income.